2011
DOI: 10.3346/jkms.2011.26.4.492
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Neural Differentiated Human Mesenchymal Stem Cells into the Cochlea of an Auditory-neuropathy Guinea Pig Model

Abstract: The aim of this study was to determine the effects of transplanted neural differentiated human mesenchymal stem cells (hMSCs) in a guinea pig model of auditory neuropathy. In this study, hMSCs were pretreated with a neural-induction protocol and transplanted into the scala tympani of the guinea pig cochlea 7 days after ouabain injury. A control model was made by injection of Hanks balanced salt solution alone into the scala tympani of the guinea pig cochlea 7 days after ouabain injury. We established the audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
0
31
2
3
Order By: Relevance
“…We found a nearly complete loss of SGNs in basal and middle turns ( Figure 5) as well as a profound shift in ABR threshold. Similar methods have recently been reported (Cho et al, 2011), but no normative data were provided on SGN loss by cochlear turn and, in contrast to our results, those authors reported no impact on sensory hair cells. We will establish a careful and systematic database of ouabain effects in the guinea pig ear that will be of broad use to other investigators exploring regenerative studies in the ouabain-treated guinea pig.…”
Section: Objective 1: Evaluate the Combination Of Genetic And Neurotrcontrasting
confidence: 54%
“…We found a nearly complete loss of SGNs in basal and middle turns ( Figure 5) as well as a profound shift in ABR threshold. Similar methods have recently been reported (Cho et al, 2011), but no normative data were provided on SGN loss by cochlear turn and, in contrast to our results, those authors reported no impact on sensory hair cells. We will establish a careful and systematic database of ouabain effects in the guinea pig ear that will be of broad use to other investigators exploring regenerative studies in the ouabain-treated guinea pig.…”
Section: Objective 1: Evaluate the Combination Of Genetic And Neurotrcontrasting
confidence: 54%
“…Cho et al delivered mesenchymal stem cells to hearing-impaired guinea pigs via the round window. They reported an increase in the spiral ganglion cells and improvement in the hearing status in ABRs (17).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the IPSCs that we used in our experiments were produced without the use of the c-myc oncogene, which might contribute to having more stable cells without teratoma formation (9). (17). Therefore, use of homograft or xenograft stem cells does not seem to affect the experiment, at least not in murine models.…”
Section: Could There Be a Difference Between Using Ipscs Or Other Typmentioning
confidence: 99%
See 1 more Smart Citation
“…Deafness animal models have been used to transplant MSCs differentiated into sensory neuronlike cells 27,33 . Indeed a useful approach for inner ear supplementation with stem cells can be hMSCs systemic application 34 .…”
Section: Hearing Recovery After Transplantation Of Mscsmentioning
confidence: 99%